2019
DOI: 10.1093/braincomms/fcz011
|View full text |Cite
|
Sign up to set email alerts
|

Recessive Charcot-Marie-Tooth and multiple sclerosis associated with a variant in MCM3AP

Abstract: Variants in MCM3AP, encoding the germinal-centre associated nuclear protein, have been associated with progressive polyneuropathy with or without intellectual disability and ptosis in some cases, and with a complex phenotype with immunodeficiency, skin changes and myelodysplasia. MCM3AP encoded protein functions as an acetyltransferase that acetylates the replication protein, MCM3, and plays a key role in the regulation of DNA replication. In this study, we report a novel variant in MCM3AP (p.Ile954Thr), in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In addition, the Sac3 variant p.Ala867Asp has been found in combination with a nonsense variant p.Tyr899* in an Australian family (AUS cell line in this study) (2) ( Figure 1C). Furthermore, peripheral neuropathy and multiple sclerosis was associated with homozygous p.Ile954Thr variant (5). Amino acid conservation of the recessive Sac3 missense variants is shown in Supplementary material, Figure S3.…”
Section: Rnamentioning
confidence: 99%
“…In addition, the Sac3 variant p.Ala867Asp has been found in combination with a nonsense variant p.Tyr899* in an Australian family (AUS cell line in this study) (2) ( Figure 1C). Furthermore, peripheral neuropathy and multiple sclerosis was associated with homozygous p.Ile954Thr variant (5). Amino acid conservation of the recessive Sac3 missense variants is shown in Supplementary material, Figure S3.…”
Section: Rnamentioning
confidence: 99%
“…9,10 It also has been found in individuals with immunodeficiency, 12 intellectual disability, 13 Alzheimer disease, 14 vascular pathologies, [15][16][17] multiple sclerosis, 17 and Charcot-Marie-Tooth disease. 4,[18][19][20] There is preliminary evidence to suggest pleiotropy in the MCM3AP gene responsible for a periodic paralysis phenotype. In 2019, Gustavasson et al reported a pathogenic MCM3AP variant segregating in a Norwegian family diagnosed with periodic paralysis.…”
Section: Clinical Neuromuscular Diseasementioning
confidence: 99%